(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In this listening assessment is consist of one part and is intended to check my students’ listening skills, and prepare real IELTS exam. Listening skills is receptive skill the is one of the most vital to acquire in English language. The objective of this listening assessment task is to enhance my learners’ listening skills and prepare IELTS exam. While doing this task, students should have enough knowledge from topic related vocabulary and grammar. In this task, students should find the correct directions from the map. This task is considered as selective listening task since students will listen to announcement from the University’s broadcast to find the correct directions. This is about four-minute audio and it will be at an appropriate level for my learners’ levels and their language proficiency. I will provide the link below.